Potential studies on the implementation of sustainable waste management in construction industry in Malaysia / Siti Hajar Quraisha Rahim - Rahim, Siti Hajar Quraisha (2014)
The Malaysian construction industry continues to grow, benefiting the country's economy and providing essential infrastructure (Papargyropoulou, Preece, Padfield,Anis, 2011). However, this industry has the biggest contribution to waste production in Malaysia. This paper focuses on the implementation of sustainable waste management in Malaysia as one way of waste management on construction site. Sustainable waste management is a process of waste management with three processes which is reduce, reuse and recycle. This is a study on the understanding of sustainable waste management process and identifies the problems in implementing it. This study aim to identify the potential of implementing sustainable waste management in construction industry in Malaysia. Sets of questionnaire were distributed to various party involve in construction industry and construction waste management with and without experienced in sustainable waste management at construction site.